Optimal Auditing, Insurance, and Redistribution - Mookherjee, Dilip; Png, Ivan (Quarterly Journal of Economics, 1989)
Dilip Mookherjee, Ivan Png; Optimal Auditing, Insurance, and Redistribution*, The Quarterly Journal of Economics, Volume 104, Issue 2, 1 May 1989, Pages 39